Rendering Mathematics for the Web using Madoko - Leijen, Daan (Proceedings of Document Engineering 2016, Vienna, Austria, 2016)
Madoko is a novel authoring system for writing complex documents. It is especially well suited for complex academic or industrial documents, like scientific articles, reference manuals, or math-heavy presentations. One particular important aspect of Madoko is to write a document in high-level Markdown with a focus on semantic content. From this document specification we can generate both high-quality PDF output (via Latex) but also generate high-quality HTML that can re-scale and re-flow dynamically. Styling is done through standard CSS attributes and can be done orthogonal to the content. Madoko provides extensive support for mathematics rendering. All math is rendered using Latex with full compatibility with any Latex packages and commands. Rendering to PDF comes this way for free but a high quality rendering of the math in the resulting HTML is more involved. This application note article describes in detail how Madoko deals with the various technical challenges. Moreover we show how other mechanisms, like replacement rules, help with creating mini domain-specific extensions to cleanly express complex math. Since this article is about the rendering of math to HTML, it is highly recommended to read this article as an HTML page instead of PDF! It can be found at http://tinyurl.com/madokomath.